Bilirubin not just a routine parameter plays an important role in chronic kidney disease - Santanu Sen; Surajit Lahiri; Saurav Dey; Swati Bhattacharyya (Asian Journal of Medical Sciences, 2024)
Background: Chronic kidney disease (CKD) is a major health burden in India as well as throughout the world. Imbalance between antioxidant defense and oxidative stress plays a major role in this multifactorial disorder. Recent studies have shown that serum total bilirubin plays an important role in the progression of CKD. Aims and Objectives: The aim of the study is to estimate serum total bilirubin, estimated glomerular filtration rate (eGFR), urea, creatinine and to find out whether there is correlation between serum total bilirubin, eGFR, and different stages of CKD. Materials and Methods: The study is conducted in the department of biochemistry after getting ethical clearance. Two hundred and sixty-nine samples of controls and cases of CKD collected. Serum total bilirubin, urea, and creatinine were calculated in autoanalyzer using standard protocol. eGFR is calculated using a standard formula. Results: There is a significant positive correlation (spearman’s correlation r=0.196, P=0.001) between serum total bilirubin and eGFR value. There is also a significant negative correlation (r=−0.239, P<0.0001) between serum total bilirubin and stages of CKD. Median value of serum urea is also high in cases compared to control. Conclusion: The serum bilirubin may be an important biomarker in the pathogenesis of CKD.